The Influence of a Low-Frequency Musical Fragment on the Neural Oscillations - DROZDENKO, Kateryna; NAIDA, Sergey; DROZDENKO, Oleksandr; DAMARAD, Anastasiia; PARENIUK, Dmytro; VAKULENKO, Liudmyla; ADARICHEVA, Zhanna (Archives of Acoustics, 2022)
Study of musical-acoustic influences, which are used to improve the functional state of a person, as well as her/his neurophysiological or psychological rehabilitation, is very relevant nowadays. It is related with a large number of conflict situations, significant psychological and informational overloads of modern human, permanent stress due to the pandemic, economic crisis, natural and man-made disasters. This work examines the effect of listening to low-frequency music on the percentage of alpha, beta, delta, and theta waves in the total spectral power of the electroencephalogram in the frequency band 0.5–30 Hz. To obtain rhythms of the brain the spectral analysis of filtered native electroencephalogram was used. For statistical analysis of neural oscillations the Student’s t-test and the sign test were implemented with usage of the Lilliefors normality criterion and the Shapiro-Wilk test. Statistically significant differences were identified in alpha, theta and delta oscillations. For the beta rhythm presented music did not play any significant role. An increase in the activity of the alpha rhythm in the temporal (for 2.20 percentage point), central (for 1.51 percentage point), parietal (for 2.70 percentage point), occipital (for 2.22 percentage point) leads of the right hemisphere and the parietal (for 1.74 percentage point) and occipital (for 2.46 percentage point) leads of the left hemisphere and also of the theta rhythm in the temporal leads of the left hemisphere (for 1.13 percentage point) were observed. The downfall of delta rhythm in the frontal lead of the left hemisphere (for 1.51 percentage point) and occipital in both hemispheres (for 1.64 and 1.33 percentage points respectively in the left and right hemispheres) was detected. These may indicate that listening to low-frequency compositions helps to restore the brain in physiological conditions at different functional overload levels, decrease the level of emotional tone, and promote relaxation.